If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+5)=5x+12
We simplify the equation to the form, which is simple to understand
3(2x+5)=5x+12
Reorder the terms in parentheses
+(+6x+15)=5x+12
Remove unnecessary parentheses
+6x+15=+5x+12
We move all terms containing x to the left and all other terms to the right.
+6x-5x=+12-15
We simplify left and right side of the equation.
+1x=-3
We divide both sides of the equation by 1 to get x.
x=-3
| 7[3-(-4x-1)]=252x+84 | | 10x-8=102 | | 8x-2(x-5)=x+5 | | 31s+10=-14s | | V^2+12v-24=0 | | 6(2t+5)=4 | | -45=-6(-36-4) | | 7n^2-52n-32=0 | | x^2-x=552 | | 20+x=2(20+x) | | (3p-4)=35 | | 2(x-5)+3(2x-8)= | | 16=8 | | 6x+24=4.7 | | 9x^2-5x= | | 16=0.5r | | x*3-6=x*12-177 | | 27y^7+24y^4=0 | | x^2-x=462 | | 4x^2-6x-10=00 | | 3c+9=6(1c+9) | | 2x+37=4x-9 | | n=-120 | | 0.66+2y=4y-0.13 | | -6x-10=2+14 | | 5(12+4)=8x | | 490=-7n | | x^2+34x+11=0 | | 3x+24=38 | | 42=14n | | X+4y=1 | | 157-2x=34x+23 |